A new species and key to species of the agriculturally important sharpshooter genus Sonesimia Young (Hemiptera: Cicadellidae: Cicadellini) - Felix, Márcio; Santos Lima, Douglas Felipe Dos; Mejdalani, Gabriel; Cavichioli, Rodney R. (Zootaxa, 2013)
The new sharpshooter species Sonesimia nessimiani is described from Bolivia based on specimens collected on sugar cane. An identification key to males and females of all known species of the genus is given. In addition to the external morphology, color pattern, and male genitalia, female genital structures are also described and illustrated. Notes comparing the new species with the remaining six Sonesimia species are provided.